2000
DOI: 10.1097/00000542-200009000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early-onset, Ventilator-associated Pneumonia in Critical Care Patients

Abstract: The authors recommend that patients undergoing emergency intubation or aspiration or who have a Glasgow coma score of 9 or less be monitored especially closely for early-onset multidrug-resistant pneumonia. The occurrence of aspiration and a Glasgow coma score of 9 or less are especially associated with pneumonia caused by A. baumanii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 1 publication
3
34
1
2
Order By: Relevance
“…24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported. [25][26][27][28][29] Our rate of 15.5% among liver recipients agrees with previously reported rates of pneumonia after LT ranging from 5% to 34%. [4][5][6][7][8][9][10]30 Two recent studies showed a rate of pneumonia of 21.1% in liver recipients receiving a 3-day prophylactic regimen of CTX and ampicillin and a rate of 18% in living donor-related recipients receiving selective digestive decontamination.…”
Section: Discussionsupporting
confidence: 92%
“…24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported. [25][26][27][28][29] Our rate of 15.5% among liver recipients agrees with previously reported rates of pneumonia after LT ranging from 5% to 34%. [4][5][6][7][8][9][10]30 Two recent studies showed a rate of pneumonia of 21.1% in liver recipients receiving a 3-day prophylactic regimen of CTX and ampicillin and a rate of 18% in living donor-related recipients receiving selective digestive decontamination.…”
Section: Discussionsupporting
confidence: 92%
“…The need for reintubation is a risk factor for the development of pulmonary infection (5,18,19) because it favors bronchoaspiration and alterations in mucociliary clearance, which may lead to bacterial contamination and colonization of the airways (14,20). Also, extubation failure is directly related to altered level of consciousness (2), probably due to the fact that patients with a lower level of consciousness exhibit large amounts of secretions, cough deficiency and swallowing deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the occurrence of extubation failure, patients with neurological disorders are usually susceptible to pulmonary complications with pneumonia being the most frequent condition (7,19,(21)(22)(23). Respiratory infection also occurs frequently after surgery and especially after neurosurgery (9,24-27).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a decreased level of consciousness, conditions are created that encourage the aspiration of germs to the lower airways, causing pneumonia. In a study using multivariate analyses, Akca et al [1] identified a decrease in the level of consciousness (OR = 3.9) and the aspiration of large volumes (OR = 12.7) among other factors responsible for hospital-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…These infections are among the main causes of in-hospital morbidity and mortality, and result in a significant increase in the mean duration of hospitalization and consequently in higher cost [1].…”
mentioning
confidence: 99%